Capital In Agriculture - Wilcox, Walter W. (Quarterly Journal of Economics, 1943)
I. Proportion of income saved and invested by farmers, 49. — II. Proportion of nation's capital employed in agriculture, 50. — Influence of interest rates, 53. — III. Prospective profits less influential than other considerations, 54. — Extent of underinvestment, 56.— IV. Influence of tenancy, 58. — Factors restricting use of credit, 58. — V. Unexploited investment opportunities, 61. — Remedial measures available, 61.